A Study of Push and Pull Factors Influencing Thai Consumers’ Purchase Behavior of Street Food: Case Study of Yaowarat (Chinatown), Bangkok - แสงธูป, พิชญา; เอกมาไพศาล, เจริญชัย (Creative Business and Sustainability Journal, 2018)
Abstract The purpose of this research was to study the push factors from consumers and the pull factors from the food and the destination environment which most influence Thai consumers of street food. The findings emphasize the relationship between the push and pull factors, and analysis of the findings then give rise to recommendations regarding how to develop street food in the Yaowarat Road (Chinatown) region of Bangkok, which is a popular and unique street food area. The recommendations are intended to benefit the stakeholders in the area (entrepreneurs and food providers) and improve the level of satisfaction for Thai customers. The study was based on a questionnaire survey collected from 270 Thai customers who purchased street food on Yaowarat Road. The study used Structural Equation Modeling (SEM) analysis, first order confirmatory factor analysis, and second order confirmatory factor analysis, as statistical tools. The study revealed that the most significant pull factor influencing Thai consumers in the Yaowarat Road area is the diversity of foods offered for sale and the pull factor is a desire to escape everyday life. The study also found that the push factor is the more influencing determinant for Thai customers visiting to consume street food in the Yoawarat Road area.